2017
DOI: 10.5455/njppp.2018.8.1143004122017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levamisole administration on immunogenic and protective capacity of Brucella abortus RB51

Abstract: Background: Brucella abortus strain RB 51 is a rough strain that was derived after multiple passages of virulent strain 2308. Levamisole, a potent anthelmintic that is widely used in veterinary medicine, is also known as an immune stimulant. Aim and Objectives: Determine the capability of levamisole to enhance the humoral antibody response and cellmediated immunity as well as protective capacity of RB 51 vaccine in mice against challenge with virulent Brucella melitensis strain. Materials and Methods: Six grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The resistant helminth against Levamisole in BSMRAU dairy farm was not developed after a third time indiscriminate treatment using different types of anthelmintics which indicates that Levamisole resistance develops at a slower rate than Fenbendazole, Ivermectin, and Triclabendazole in dairy cows. The probable reason for the different findings on Levamisole might be due to the immune stimulant properties of Levamisole (Mansour, 2018). These findings indicate that Levamisole is still effective for the treatment of dairy cows in Gazipur, Bangladesh.…”
Section: Discussionmentioning
confidence: 87%
“…The resistant helminth against Levamisole in BSMRAU dairy farm was not developed after a third time indiscriminate treatment using different types of anthelmintics which indicates that Levamisole resistance develops at a slower rate than Fenbendazole, Ivermectin, and Triclabendazole in dairy cows. The probable reason for the different findings on Levamisole might be due to the immune stimulant properties of Levamisole (Mansour, 2018). These findings indicate that Levamisole is still effective for the treatment of dairy cows in Gazipur, Bangladesh.…”
Section: Discussionmentioning
confidence: 87%
“…Oral or injectable administration of levamisole has been studied for weight gain, mucosal protection by assessment of IgA status, and humeral immune stimulation at different ages in pigs [41] . Concomitant use of levamisole with viral and bacterial vaccines in pigs has shown that levamisole not only improves antibody production but also increases the half-life of antibodies in pigs [43– 46] . Interestingly, levamisole reduced cortisol levels after experimentally induced stress on pigs for 16 days.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the endometriosis pathophysiology is not very clear, and it is believed that endometrial cells evade apoptosis and the immunosurveillance system in the peritoneal cavity [65] . Recent studies have revealed that several factors contribute to endometriosis, including reduced T cell reactivity and natural killer cytotoxicity, activation of B cells, elevated antibody production, increased number and activation of peritoneal macrophages, and alterations in inflammatory mediators [46] . Levamisole was used in experimental endometriosis, either alone or in combination with other agents, as a treatment approach.…”
Section: Resultsmentioning
confidence: 99%